Mindscapes of Learning: Gender, the Creative Imagery Ability, and the Embodied Nature of Academic Success - KARTAL, Osman Yılmaz; YAZGAN, Akan Deniz; TEMELLİ, Dinçer; KARTAL, Meral YAVUZ; BULUT, Beyza; ŞAHİN, Çavuş (Journal of Ecohumanism, 2024)
This particular study sets out to investigate thoroughly the intricate and fascinating relationship that exists between the abilities of creative imagery and the academic performance of the eighth graders; especially for the male and female learners and how they perform in relation to their imaginative abilities and academic achievement. The research was done among a total of 105 eighth-grade middle school learners which included 52 boys and 53 girls drawn from a public middle school situated in the moderate socio-cultural as well as the socio-economic context of Çanakkale, Turkey. The results of this particular study have revealed that overall, girls do much better than boys on Vividness and Transformation with significantly higher means in these two dimensions while for Originality, the findings indicate that there are no significant gender factors. As regards academic achievement, significant gender-based differences were also observed, as girls eclipsed boys in Turkish, Mathematics, and Science with overall better performance percentages. The study further showed that there is a positive relationship between the creativity capacities of male participants which implies that the high-performance levels of such students can be directly linked to their creative imagination abilities whereas this correlation was not observed in female participants.